Severity of Acute Infectious Mononucleosis Correlates with Cross-Reactive Influenza CD8 T-Cell Receptor Repertoires - Nuray Aslan (American Society for Microbiology, 2017)
ABSTRACT Fifty years after the discovery of Epstein-Barr virus (EBV), it remains unclear how primary infection with this virus leads to massive CD8 T-cell expansion and acute infectious mononucleosis (AIM) in young adults. AIM can vary greatly in severity, from a mild transient influenza-like illness to a prolonged severe syndrome. We questioned whether expansion of a unique HLA-A2.01-restricted, cross-reactive CD8 T-cell response between influenza virus A-M158 (IAV-M1) and EBV BMLF1280 (EBV-BM) could modulate the immune response to EBV and play a role in determining the severity of AIM in 32 college students. Only ex vivo total IAV-M1 and IAV-M1+EBV-BM cross-reactive tetramer+ frequencies directly correlated with AIM severity and were predictive of severe disease. Expansion of specific cross-reactive memory IAV-M1 T-cell receptor (TCR) Vβ repertoires correlated with levels of disease severity. There were unique profiles of qualitatively different functional responses in the cross-reactive and EBV-specific CD8 T-cell responses in each of the three groups studied, severe-AIM patients, mild-AIM patients, and seropositive persistently EBV-infected healthy donors, that may result from differences in TCR repertoire use. IAV-M1 tetramer+ cells were functionally cross-reactive in short-term cultures, were associated with the highest disease severity in AIM, and displayed enhanced production of gamma interferon, a cytokine that greatly amplifies immune responses, thus frequently contributing to induction of immunopathology. Altogether, these data link heterologous immunity via CD8 T-cell cross-reactivity to CD8 T-cell repertoire selection, function, and resultant disease severity in a common and important human infection. In particular, it highlights for the first time a direct link between the TCR repertoire with pathogenesis and the diversity of outcomes upon pathogen encounter. IMPORTANCE The pathogenic impact of immune responses that by chance cross-react to unrelated viruses has not been established in human infections. Here, we demonstrate that the severity of acute infectious mononucleosis (AIM), an Epstein-Barr virus (EBV)-induced disease prevalent in young adults but not children, is associated with increased frequencies of T cells cross-reactive to EBV and the commonly acquired influenza A virus (IAV). The T-cell receptor (TCR) repertoire and functions of these cross-reactive T cells differed between mild- and severe-AIM patients, most likely because these two groups of patients had selected different memory TCR repertoires in response to IAV infections encountered earlier. This heterologous immunity may explain variability in disease outcome and why young adults with more-developed IAV-specific memory T-cell pools have more-severe disease than children, who have less-developed memory pools. This study provides a new framework for understanding the role of heterologous immunity in human health and disease and highlights an important developing field examining the role of T-cell repertoires in the mediation of immunopathology.